A Study on Measuring Impact of Users Satisfaction on Us ERS Loyalty of India Post Payment Bank (Trinity Journal of Management, IT & Media (TJMITM), 2024)
Loyalty towards an organization determines its growth and furthers the possibilities  of being a successful organization. Banking services are entirely dependent on the  user’s satisfaction and user loyalty. The purpose of this research is to measure the  impact of user’s satisfaction on user’s loyalty of India Post Payment Bank. The  technique used for the current study is structural equation model using SMART  PLS. According to the study’s findings, customer satisfaction appears to have a  favourable, considerable influence on customer loyalty.
Keywords: User satisfaction; User loyalty; Payment banks; IPPB